Evaluasi Hasil Penerapan Rancangan Penyuluhan Tentang Pengaplikasian Pakan Fermentasi Gedebog Pisang Untuk Sapi Potong Desa Tambaksari Kecamatan Purwodadi Kabupaten Pasuruan - Rezki amalyadi; Ismulhadi; Wahyu Windari (Fakultas Peternakan, Universitas PGRI Kanjuruhan Malang, 2022)
The study aims describe evaluation the results implementation of extension design on the application banana stem fermented feed for beef cattle tambaksari village, purwodadi district, pasuruan regency. Variable observed are whether the material, methods and media are determined according to the target needs. The study population was 60 people and sampling used Total Sampling. Research method used descriptive quantitative. Data taken primary and secondary data where collection’s through interviews, observation and questionnaires. Counseling design based on the potential of natural resources and human resources that are owned by the target where in general target is elementary education, 45 years old and 10 years old. Stated goal is the goal of good perception feed fermentation of banana stem for fattening of beef cattle. Material determined through several stages includes identifying problems and solving them, testing priority problems, determining factors, grouping agricultural extension materials, selecting / selecting agricultural extension materials based on the subject matter, grouping agricultural extension materials based on material characteristics, and decision-making matrices. The media used in counseling is determined using a matrix Analysis of the determination of agricultural extension media. Method used in counseling is determined using consideration of the selection of agricultural extension methods. The media used are Power Point, Video and Leaflets. While the methods used are lectures, group discussions, demonstrations of ways and direct practices. Evaluation results showed (100%) farmers stated that the determination of material, media, and methods used in counseling with consideration to the conditions of the goals and objectives of counseling in accordance with what was needed so that the material could be accepted by the extension targets. All farmers state the material, media and methods according to their needs. So that it is expected that the material given in counseling can be applied in livestock business.